Development of Bra Pressure Measuring: System Using Air Pressure Sensor - Luu Thi, Hong Nhung; Nguyen Nhat, Trinh; Nguyen Thi Dieu, Linh; Nguyen Thi, Le (Ingeniería Solidaria, 2020)
Introduction: This paper is the result of the research “Development of bra pressure measuring system using air pressure sensor” developed in the Ha Noi University of Science and Technology in 2019. Problem: The pressure of the bra on the human body affects the comfort of the wearer and the wearer's health. Therefore, bra pressure is one of the most important parameters taken into account when designing and manufacturing bras.Objective: To determine the pressure value of a bra, it is necessary to use a suitable pressure measuring device.Methodology: The device operates on the principle of resitive gas pressure sensor, with 8 measuring channels. The system is controlled by the computer via programming software in the Visual C language, measuring the pressure of the shirt on the position on the curved surface of the human body. Pressure values ​​and timed charts are displayed on the computer. The measuring device was tested with GE Druck DPI 610 pressure generator. Results: Test results showed that the device has a sensitivity of 0.01 kPa, measuring range from 0.1to 10 kPa and an accuracy of 0.01 kPa.Conclusion: This measurement system is important for objectively assessing the pressure of the bra on the wearer. Originality: This paper presents the results of research and design of the PB228 system when measuring the pressure of the bra on the wearer's body in static, dynamic and static-dynamic combined states. Limitations: The accuracy of the device only applies in standard conditions
Keywords: Bra; bra pressure; air pressure sensor; pressure measuring device